Xica da Silva revisitada: o olhar de um outro tempo no romance biográfico de Ana Miranda - Ribeiro, Josiane de Oliveira Pinto (2021)
Among the numerous works by contemporary writer Ana Miranda, Xica da Silva: A Cinderela Negra (2016) strongly represents what we believe to be the author's literary project, as her narratives, in different ways, provide new perspectives on personalities or anonymous people in history from Brazil. The work portrays differently the life of the ex-enslaved woman who became the partner of the contractor of the diamond mines and the one who actively participated in the society of the Diamantino District, in Minas Gerais, in the Brazilian colonial period of the 18th century. Initially known through oral narratives, the protagonist had her image represented in various ways until becoming an object of more detailed study for historiography. Therefore, based on Linda Hutcheon's proposal, which names contemporary productions focused on historical themes such as "historiographical metafiction" (HUTCHEON, 1991), and understanding Ana Miranda's work from a contemporary perspective, from Agamben (2009) and Schøllhammer (2009), this work aims to develop an analytical-interpretative reading of Ana Miranda's work aiming to place it in the postmodernist context proposed by Hutcheon, from the historiographical perspective and the crossing of historical and fictional discourses. Furthermore, to understand the hybridity of genres, given the classification of the work as "biography" and its effective realization in dialogue with fiction, and also how the presence of the "ex-centric" and the concept of adaptation corroborated the redefinition of the story of Xica da Silva.